2020
DOI: 10.1007/s10457-020-00562-x
|View full text |Cite
|
Sign up to set email alerts
|

Using a multi-stakeholder approach to increase value for traditional agroforestry systems: the case of baobab (Adansonia digitata L.) in Kilifi, Kenya

Abstract: The baobab tree (Adansonia digitata L.) is an integral component of many dryland farming systems in sub-Sahara Africa. Such traditional agroforestry systems can foster a variety of benefits; besides positive livelihood implications baobab can particularly address food security objectives due to its highly nutritious fruits. However, many bottlenecks persist inhibiting the broader potential of indigenous trees in farming systems and their increased utilisation and commercialisation. We suggest that traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Similarly, Azam-Ali (2007) indicated that the adoption of multi-cropping systems with indigenous crops is critical in combating climatic risks. Indigenous people are important in agroforestry programs of indigenous fruit trees (Jusu and Cuni-Sanchez, 2017; Meinhold and Darr, 2020). Agroforestry can be an opportunity for implementing afforestation and reforestation projects that are important in addressing deforestation and desertification threats in SSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Azam-Ali (2007) indicated that the adoption of multi-cropping systems with indigenous crops is critical in combating climatic risks. Indigenous people are important in agroforestry programs of indigenous fruit trees (Jusu and Cuni-Sanchez, 2017; Meinhold and Darr, 2020). Agroforestry can be an opportunity for implementing afforestation and reforestation projects that are important in addressing deforestation and desertification threats in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…Similar calls for interventions to unlock the potential of indigenous and traditional foods are made by Cloete and Idsardi (2013). More efforts toward value addition and marketing to realize the full benefits of such foods need to be considered (Dovie et al , 2007; Meinhold and Darr, 2020). Overall, individual countries need to formulate and strengthen policies that promote the continued use of IK in food systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars have been stressing the role of the development of new business models (BMs) in agroforestry and tourism activities, as part of an inclusive and sustainable approach, as an effective economic driver in the structurally weak low-density rural regions [17,18]. This would enable them to attract people and new business to the region and to promote its sustainable development, a concept that integrates the social, economic and environmental spheres [19].…”
Section: Literature Review 21 Low-density Rural Regionsmentioning
confidence: 99%
“…However, bottlenecks limit the benefits from indigenous fruits produced in traditional agroforestry systems [91], among them market insufficiencies and failures such as limited demand, inadequate supply, and marketing channels or supply control mechanisms [92][93][94]. One strategy to realize the potential of native fruit tree species in traditional agroforestry systems to enhance food security, livelihoods, and resilience for future challenges, is to stimulate emergence of markets and development and promotion of businesses and innovations to meet the arising market demand [95].…”
Section: Agroforestsmentioning
confidence: 99%